KEPENTINGAN EKONOMI POLITIK RUSIA BERGABUNG DALAM WORLD TRADE ORGANIZATION (WTO) TAHUN 2008-2012 - Khothibulloh Muhammad; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
After the disintegration  of the Soviet Union, Russia had begun some major transformation in its political  and economic structure. One of the biggest change in the transformation was the effort of Russian accesion into the World Trade Organization. Overview of Russian energy policy in view of it‟s WTO accession.  This study used qualitative research methods that the source data is taken from books, journals, newspapers, internet, and previous research has relevant data with the title.Perspectives and levels of analysis used in this study is that the state and NGO as the main actor.  By using the concept national interest and theory of theory of international cooperation, will describe the direction of the object of analysis. This study will explain the factors that led  the Russia accession in WTO.  The transition from the Soviet Union to the Russian Federation reinforced the influence of energy resources on Russia‟s economic growth. Regional economic integration and WTO accession have been treated as complementary strategies by the Russian government since the early 2000s. The emergence of Eurasian Economic Community (EurasEC) has created challenges for Russia‟s integration into the world economy given Gazprom‟s market dominance in the Russian economy. Reforming Gazprom‟s pricing system requires both domestic political will and external incentives that will compensate for price reductions in international markets. Keywords :    Russian Federation,  National interest, accession WTO,  Eurasian Economic Forum, International market